Increased Expression of the E3 Ubiquitin Ligase RNF5 Is Associated with Decreased Survival in Breast Cancer - Bromberg, Kenneth D. (2007)
The selective ubiquitination of proteins by ubiquitin E3 ligases plays an important regulatory role in control of cell differentiation, growth, and transformation and their dysregulation is often associated with pathologic outcomes, including tumorigenesis. RNF5 is an E3 ubiquitin ligase that has been implicated in motility and endoplasmic reticulum stress response. Here, we show that RNF5 expression is upregulated in breast cancer tumors and related cell lines. Elevated expression of RNF5 was seen in breast cancer cell lines that became more sensitive to cytochalasin D– and paclitaxel-induced apoptosis following its knockdown with specific short interfering RNA. Inhibition of RNF5 expression markedly decreased cell proliferation and caused a reorganization of the actin cytoskeleton in response to stress in MCF-7 but not in p53 mutant breast cancer cells, suggesting a p53- dependent function. Significantly, high levels of RNF5 were associated with decreased survival in human breast cancer specimens. Similarly, RNF5 levels were higher in metastatic melanoma specimens and in melanoma, leukemia, ovarian, and renal tumor-derived cell lines, suggesting that increased RNF5 expression may be a common event during tumor progression. These results indicate that RNF5 is a novel regulator of breast cancer progression through its effect on actin cytoskeletal alterations, which also affect sensitivity of breast cancer cells to cytoskeletal targeting antineoplastic agents.